Novas metodologias de pesquisa para validar a importância do teor de materiais voláteis e de carbono fixo em materiais lignocelulósicos. - Silva, Diego Aleixo da (2023)
Brazil has potential for the cultivation of various biomasses of energy interest. Knowledge of the best energy parameters to evaluate a lignocellulosic biofuel is essential for this new scenario. Immediate analysis is a simple and inexpensive methodology to provide information for different fuels. The objective was to bring new interdisciplinary analyzes to have a holistic interpretation of the parameters that make up the immediate analysis. In the first chapter, a bibliographic review about lignocellulosic biomass was elaborated; context in the world and national matrix, chemical composition of the macrocomponents, immediate analysis, calorific value, elemental analysis. In the second chapter two, different analyzes were tested in the field of forest fires, seeking to establish an association with parameters of immediate analysis. Ten different types of lignocellulosic biomass were used. There was a strong correlation between the content of volatile materials and the ignition time and duration of flame of the tested biomasses. In chapter three, an isothermogravimetric analysis was tested in a muffle furnace. Tectona grandis biomass was used at six different temperatures in order to generate different values of fixed carbon. The correlation of fixed carbon with the time of thermal degradation of different materials was confirmed. In chapter four, an approach was made to the influence of humidity on biofuel. The results showed that higher humidity caused a longer ignition time and a shorter fuel flame duration. In the isothermogravimetric analysis it was observed that in the first thirty seconds the material loses all its moisture. In drier biomasses, part of the volatiles is also lost at the same time. Which is responsible for releasing the volatile flammable material that accelerated its ignition against the most humid biomasses. It is concluded that new methodologies were created and can be worked together with the immediate analysis